2017
DOI: 10.2527/jas2017.1603
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antioxidant mixtures in the diet of finishing pigs on the oxidative status and shelf life of longissimus dorsi muscle packaged under modified atmosphere1,2

Abstract: The effect of pig dietary supplementation with an antioxidant mixture (AOX), containing vitamin E and verbascoside, on animal oxidative status, meat quality parameters, and shelf life of the longissimus dorsi (LD) muscle was examined. Seventy pigs with an average live weight of 95.2 ± 1.2 kg were selected and assigned to 2 dietary treatments. The control (CTR) group was fed a commercial diet, and the AOX group was fed the same diet supplemented with the AOX, containing vitamin E and verbascoside from Verbenace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…The physical parameters such as pH, colour and water‐holding capacity (WHC) were evaluated in the same animals on the target muscle Longissimus dorsi 10 . The pH values and WHC were not affected by dietary treatments and the colour parameters showed a colour‐stabilizing effect of the AOX mixture during refrigerate storage of samples packed in a modified atmosphere.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The physical parameters such as pH, colour and water‐holding capacity (WHC) were evaluated in the same animals on the target muscle Longissimus dorsi 10 . The pH values and WHC were not affected by dietary treatments and the colour parameters showed a colour‐stabilizing effect of the AOX mixture during refrigerate storage of samples packed in a modified atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…The growth performance and carcass characteristics have been previously reported 10 . After an on‐farm fasting period of 8 h, the pigs were individually weighed and transported for 2 h to the abattoir.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported no effects of dietary supplementation with polyphenols on carcass characteristics in pigs and rabbit [ 9 , 33 ]. Other studies in pigs reported an enhancement of carcass characteristics due to polyphenols supplementation [ 34 , 35 ]. These different results are probably due to the length and dosage of dietary supplementation and the active principles content of the plant extract used.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation is important for the health of the pig, in particular vitamin E which is a potent antioxidant, helping to keep the pig healthy and enriching the vitamin E content of the muscle (Wang et al 2012). Vitamin E also improves drip loss (fluid that is lost from a piece of meat without adding any force) in the meat and enhances the shelf life of raw pork by preventing oxidative deterioration (Rossi et al 2017). Lipid oxidation of pork meat can be a problem when feeding pigs certain grains such as distillers dried grains; however, supplementation with vitamin E has been shown to reduce these effects (Boler et al 2009).…”
Section: Resultsmentioning
confidence: 99%